ECONOMIC ACTIVITIES OF KUNGRAT SURKHAN OASIS (TAMADDUN NURI JURNALI, 2024)
In the article, the economic activities of the Kungrats of the Surkhan oasis contain an analysis of the structure of agriculture and the rituals associated with it, as well as traditional and modern features of the primordial animal husbandry activities and handicrafts of the Kungrats of the oasis.